Critical Analysis of Laboratory Biomarker Discovery: Bridging Biomedical Research with Clinical Diagnostics for Early Disease Detection - Al Ghamdi , Abdulaziz Saleh M; Alalawi , Rayan Omar; Almalki , Ahmad Safar A; Alzahrani , Abdulrahman Mashni; Nezamuldeen , Abdulfattah; Alshikhey , Mohammad Ahmad; Hassanin , Khalid Faisal; Alzahrani , Abdulwahab Mohammed; Almotairi, Mamdouh Saeed H; aljowhari , Sultan Mohammed; Alzahrani , Adnan Ahmed; Sharia, Faisal Hadi H Al (Journal of Ecohumanism, 2024)
Biomarkers are well-defined molecular targets that are essential for the early diagnosis of diseases, as well as for prompting appropriate treatments and assessing the disease states. Using biomarkers identified in laboratory models with clinical diagnostic tools has successfully enhanced the health delivery system. This paper will revisit the progress made in biomarker discovery about research methodologies, current challenges, and development in light of emerging trends in using biomarkers in biomedical research and clinical practice. Based on a literature review of current publications and methodological approaches supplemented by analysis of case studies in this work, the main issue of the slow transition from the discovery of knowledge to clinical practice is stated, and potential papers’ solutions are suggested to address this problem. Numerical data, figures, tables, and graphs explain patterns and results.